2000
DOI: 10.1021/ol0056527
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioselective Michael Reactions Catalyzed by a Chiral Quaternary Ammonium Salt. Illustration by Asymmetric Syntheses of (S)-Ornithine and Chiral 2-Cyclohexenones

Abstract: [formula: see text] The use of the chiral quaternary ammonium salts 1a and 1b makes possible enantioselective Michael reactions which have been applied to the asymmetric syntheses of (S)-ornithine (2) and the chiral 2-cyclohexenone 6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
78
0
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(87 citation statements)
references
References 10 publications
1
78
0
8
Order By: Relevance
“…[3] Corey et al first reported the conjugate addition of 1 to acrylates and enones with notable enantioselectivity (> 90 % ee) in the presence of an Nalkylated cinchonidine salt. [4] Subsequently, the scope of the reaction was expanded with other modified cinchona alkaloids [5] as well as new catalysts, comprising largely of quaternary bis(ammonium) and N-spiro ammonium moieties derived from tartrates, [6] axially-chiral 1,1'-biaryl units, [5f, 7] inositol-derived crown ethers, [8] and a calix[4]arene amino acid. [9] The use of these pH-neutral catalysts requires strong bases to generate the nucleophile, thus very low temperatures (typically À40 to À78 8C) were necessary to suppress competitive reactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[3] Corey et al first reported the conjugate addition of 1 to acrylates and enones with notable enantioselectivity (> 90 % ee) in the presence of an Nalkylated cinchonidine salt. [4] Subsequently, the scope of the reaction was expanded with other modified cinchona alkaloids [5] as well as new catalysts, comprising largely of quaternary bis(ammonium) and N-spiro ammonium moieties derived from tartrates, [6] axially-chiral 1,1'-biaryl units, [5f, 7] inositol-derived crown ethers, [8] and a calix[4]arene amino acid. [9] The use of these pH-neutral catalysts requires strong bases to generate the nucleophile, thus very low temperatures (typically À40 to À78 8C) were necessary to suppress competitive reactions.…”
mentioning
confidence: 99%
“…Herein, we describe the preparation of a family of structurally novel 2-oxopyrimidinium salts (5), and their performance as asymmetric PTCs in the conjugate addition of the glycine imine ester 1 a (R 1 = tBu) to vinyl ketone and chalcone derivatives.…”
mentioning
confidence: 99%
“…The absorbance values of the studied amino acid are given in table ( 2) and shown in figures 4, 5, and 6.…”
Section: Resultsmentioning
confidence: 99%
“…Altering the charge on amino acids and their derivatives by varying the pH facilitate the physical separation of amino acids, peptides and proteins. 2 The isoelectric species is the form of a molecule that has an equal number of positive and negative charges and thus is electrically neutral. The isoelectric pH, also called the pI is the pH midway between pKa values on either side of the isoelectric species.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of Schiff base to vinyl cyanide furnished the key precursor of ornithine in 91% ee. 79 Remarkably, the stereogenic center did not racemize under the reaction conditions, despite the high acidity of the proton of the chiral center.…”
Section: Synthesis Of 175mentioning
confidence: 95%